2017
DOI: 10.4174/astr.2017.93.4.186
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcome and prognostic factors of neoadjuvant treatment followed by resection for borderline resectable pancreatic cancer

Abstract: PurposeNeoadjuvant treatment may provide improved survival outcomes for patients with borderline resectable pancreatic cancer (BRPC). The purpose of this study is to evaluate the clinical outcomes of neoadjuvant treatment and to identify prognostic factors.MethodsForty patients who met the National Comprehensive Cancer Network definition of BRPC and received neoadjuvant treatment followed by surgery between 2007 and 2015 were evaluated. Prospectively collected clinicopathological outcomes were analyzed retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…[ 17 , 25 ] In addition, patients with partial response showed better OS than patients with stable disease (33.7 vs 17.5 months, P = .04), and similar results have been previously reported. [ 26 ] On the basis of these results, pancreatectomy with AR could be particularly useful in patients with partial response after neoadjuvant chemotherapy. In the subgroup analysis according to operation type, the oncologic outcome was better in the neoadjuvant chemotherapy group after PD and TP, but not after DP.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 , 25 ] In addition, patients with partial response showed better OS than patients with stable disease (33.7 vs 17.5 months, P = .04), and similar results have been previously reported. [ 26 ] On the basis of these results, pancreatectomy with AR could be particularly useful in patients with partial response after neoadjuvant chemotherapy. In the subgroup analysis according to operation type, the oncologic outcome was better in the neoadjuvant chemotherapy group after PD and TP, but not after DP.…”
Section: Discussionmentioning
confidence: 99%
“…15,24 In a meta-analysis, the rate of R0 resection in BRPC patients after receipt of neoadjuvant therapy was 54%. 21 In another study on 15 BRPC patients who underwent resection, one (7%) underwent an R1 resection.…”
Section: Discussionmentioning
confidence: 99%
“…The latter could serve as a good prognostic factor to be confirmed by analysis of bigger data sets. As previously reported, the levels of Ca 19-9 at the onset of the disease may represent an interesting prognostic factor [9]. Spinelli et al reported a case of a long term survivor with more than 10 years after diagnosis of PEC with metastatic disease, but unfortunately there is no mention of Ca 19-9 levels [10].…”
Section: Discussionmentioning
confidence: 86%